stela maria de paiva carrijo: vida, lugares de formação e carreira docente - Borges, Jullizze Maia (2024)
The present research focuses on the study of Literacy and aims to contribute to the production of knowledge in the field of History and Historiography of Education. It specifically centers on the life trajectory of the literacy teacher Stela Carrijo, with an emphasis on her history, places of education, and teaching career. This emphasis is justified because, despite her contributions to the history of literacy being noticeable in the municipality of Uberlândia, there is still a scarcity of research and records that contribute to understanding and sharing her practices. As a research methodology, it relies on the approach of Life Oral History, seeking narratives from individuals who lived with the biographee. The selection criteria include the following: being a relative (daughter or son) of the biographee; having been a student of the biographee during academic training; having worked as a teacher in the institution where the biographee was a manager; and also having worked as a colleague in teaching and educational management. Four collaborators were selected. In parallel with the Oral History research, bibliographic and documentary research was conducted. The triangulation of oral and documentary sources supported the weaving of the life history, being and becoming, of teacher Stela Carrijo, as an everyday literacy teacher. The narratives of all interviewees unanimously affirm the importance of Stela Carrijo and her practices for literacy. The research not only contributes to doing justice by recognizing the contributions of the biographee but also helps address gaps and shortcomings in the historiography of literacy in Uberlândia. These gaps and shortcomings became evident when searching for sources and studies documenting literacy practices, the educational trajectory, and contributions to the field by Stela. The scarcity of records and bibliographic references addressing Stela's educational and literacy activities in Uberlândia became apparent.